The Road to Reconciliation—Insights from Christian Public Theology - Christine Schliesser (Religions, 2022)
Once primarily situated within religious contexts, reconciliation has since become an established concept in peace and conflict studies. The exact meaning of this concept remains disputed. This contribution takes the sometimes heated debates one step back as it seeks to return to the roots of the religious dimensions of reconciliation in order to shed light on its meaning and use for peace and conflict studies today. Using Christian Public Theology as a framework, the author delineates several hallmarks on the road to reconciliation. While the metaphoric “road to reconciliation” must not be misunderstood as a linear progression with a predictable result, it does indicate that certain milestones are likely to be encountered on this path. These include remembrance, repentance, confession of guilt, forgiveness and justice. As the author draws out the religious dimensions of these concepts, a deeper understanding of the meaning of reconciliation emerges.